Creative Hub in South Tangerang City and its Biophilic Architectural Theme - Shavrizal, Shavrizal (Journal of Aesthetics, Creativity and Art Management, 2024)
Banten Province in Indonesia is one of the ninth contributors to the creative economy where South Tangerang City has become one of the centers of creative economic growth in Jabodetabek (Jakarta, Bogor, Depok, Tengerang, Bekasi) with its main fields, the crafts sub-sector, the architecture sub-sector and the start-up sub-sector. Regarding the three main sub-sectors, this research is intended to create a centralized and integrated forum for people to develop their talents and businesses. This research method is qualitative. The Creative Hub in South Tangerang City is a place for creative economy actors to develop their talents and businesses. Using a biophilic architectural theme, the site design is a part of the development of the economic and business center in South Tangerang City. The site covers offices, shopping outlets and restaurants.